A Study on User Intention to Commute Using Autonomous Rail Transit - Siti Nur Fatin, Morshidi; Nur Zaimah, Ubaidillah; Farhana, Ismail; Rossazana Ab-Rahim, Ab-Rahim (2022)
This study aims to investigate the user intention to commute using Autonomous Rail Transit in Sibu, Sarawak. The variables that are brought into this study are subjective norm, perceive behavioral control, attitude, and environmental concern. The PLS-SEM software are employed to determine the user intentions within 350 targeted respondents which are residing in Sibu, Sarawak. According to the findings, subjective norm, perceived behavioural control and attitude are significant towards user intention. As a result, policymakers must improve transportation demand management, establish urban growth boundaries, and provide incentives for sustainable transport. This is to encourage people to commute Autonomous Rail Transit in Sibu, Sarawak in the future.